ANALISIS SWOT DALAM MENENTUKAN STRATEGI BERSAING PADA PT BANK SUMSEL BABEL PALEMBANG - Yoskario pratama; Omar hendro; Endah dewi purnamasari (Jurnal Ilmiah Ekonomi Global Masa Kini)
The competitive strategy is one way to know its competitiveness in every strength.The effective use of Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis can play an important role in determining a competitive strategy, especially to know the strengths, weaknesses, opportunities and threats the company faced in maintaining the sustainability and continuity of the company. This study aims to determine the SWOT analysis in determining competitive strategy at PT. Bank Sumsel Babel Palembang.The result of this research showed that the internal factor in determining the competitive strategy at PT. Bank Sumsel Babel Palembang comprised of strengths including: Good Corporate Governance and Bank behavior or culture, Positive Investment Climate and high morale, Positive Contribution to the community and environmental sustainability. And weaknesses include: Limited expertise, Lack of supporting facilities, Lack of supporting rules. Then from external factors in determining competitive strategy at PT. Bank Sumsel Babel Palembang comprised of opportunities include: Majority of the Palembang people, by having a Cooperate, it will result the High Potential Communities. And threats include: Total share banking, Lack of understanding about syariah banking, Social impression on banks.Keywords: Competitive, Strategy, SWOT Analysis